(untitled) (Archaeologia Adriatica, 2010)
The panels of the baptismal font in the Split baptistery are in secondary use; they originally functioned as plutei – sections of the altar screen. All the panels are covered by abstract interlaced patterns except for one, which depicts three human figures, one of them a king on a throne. One of the panels, incompletely preserved, broken into two pieces, and embedded into the step in front of the altar of the baptistery most probably originated from the cathedral of Split. One fragment of a panel - pluteus from the Split cathedral would connect to the fragment of the panel from the step in front of the baptistery altar, so they most likely were part of the same unit. The origin of the panels for the baptismal font is unknown (they could be from different places). Nor is it known when they were secondarily used to build the baptismal font. It can be hypothesized with certainty only for one, the fragment built into in the step, that it originally came from the Split cathedral. The greatest attention is drawn to the relief depicting a king. Analysis of this relief has shown that an inscription was removed. It was also noted that the figure next to the king originally held an object in his hands, probably a scroll, which was also subsequently chipped off. The figure of the ruler has been variously identified as a Croatian king (Petar Krešimir IV, Zvonimir…), as a Byzantine emperor, as Charlemagne… The hypothesis seems particularly possible that King Zvonimir was depicted, considering his coronation in Solin in 1075, when he received his royal insignia from the pope. Conjectures are also frequent that this represents the Savior in glory, the figure of Christ, or even some Christian symbolism. A hypothesis was also suggested that the image of a ruler was in fact an illustration of an analogy from the Gospels about a cruel debtor who did not forgive his debtor (Mt. 18, 23-35), so that this would depict a king with the merciless debtor kneeling in front of him. The figure of the king from the story would, however, be an allusion to Christ as the heavenly king. Hence the relief with the figure of a king would not depict some specific secular ruler. Different hypotheses exist about the provenience of the panels: they would originally have been plutei of the altar screens of the Coronation Basilica in Solin (the Church of SS. Peter and Moses, at the site of the Hollow Church), from the monastery church of St. Euphemia in Split, from the Split cathedral … A new hypothesis is presented in this article. Some of the panels from the Split baptistery may have come from the demolished monastery church of St. Peter in Jesenice (sanctus Petrus in Sello/Selle, sanctus Petrus de Gumai, de Gumag…), which was founded by the magnate Petar Črnjin called Gumaj (Petrus Zerni qui et Gumai filus). The monastery church was quite large and three-aisled; many panels could have been in its altar screen. On one of these panels, which originally would have stood in the most prominent place in the church, by the entrance in the altar screen, it is possible that Petar Črnjin, King Zvonimir, and an individual (Streza) who had lost a dispute would have been represented. In fact, Petar Črnjin had a dispute in 1078 documented in Šibenik that was to be decided by King Zvonimir; the quarrel was with Streza – the king’s uncle, who had attempted to grab some land. But it is also possible that it is King Slavac who is depicted, and the prostrated individual could perhaps have been one of the Neretva tribe who had also lost a dispute with Petar Črnjin. After the monastery was closed in the 13th century, when the monastery estates were acquired by the archdiocese of Split, a new church was built at the same place in the 14th century, but to a much smaller scale. It is possible that some of the altar screen panels were then transported to Split, to be used as the panels of the baptismal font. On that occasion, the inscription that may have mentioned a king was probably removed.